Evaluation of antioxidant and toxic potentials of aromatic amides synthesized following Green Chemistry (Research, Society and Development, 2022)
Organic synthesis corresponds to the largest means of production of new drugs in therapeutics currently available on the market, thus, thinking about production processes that aim at less harm to the environment and generation of waste is essential, especially of aromatic amides that are classically synthesis products generate waste, and are widely applied in the chemical and pharmaceutical industry in general. This study analyzed the antioxidant and toxic potential of five aromatic amides synthesized following the precepts of Green Chemistry - by the Schotten-Baumann method, and their structure-activity relationship was highlighted to explain the patterns found in the study. We emphasize that two of them showed promising results for the antioxidant and toxic test, and may go ahead in future studies that safely test their applications and uses as bioactive compounds, and it is noteworthy that both are considered unprecedented in the literature to date, establishing, therefore, the important link between alternative green production routes for the industrial mode and the environment.